Press release writing training in Sriwedari Village - Muadz Muadz; Buddy Riyanto (Universitas Muhammadiyah Magelang, 2022)
Sriwedari Village, in the heart of Surakarta City, has all of the necessary public amenities to support a wide range of community activities, including wayang orang performances, museum visits, sports competitions, and music concerts. If it is published in the media, this could actually be positive news for Sriwedari Village. Furthermore, in Sriwedari Village, the community's various activities have not been matched by the ability to publish in the mass media. This community service aims to provide training in the ability to write press releases and media relations for residents of Sriwedari Village, Surakarta. In the midst of the covid-19 pandemic, this Community Service is carried out both offline and online. Residents of Sriwedari Village who are members of the Sriwedari Village Children and Youth Forum took part in this activity. Identifying partner problems, providing materials, hands-on training on press release writing, and evaluation are all stages of program implementation. This press release writing training activity went off without a hitch. It is clear that the majority of the participants know how to write a good press release.